2011
DOI: 10.2139/ssrn.1470768
|View full text |Cite
|
Sign up to set email alerts
|

Social Structure of Facebook Networks

Abstract: We study the social structure of Facebook "friendship" networks at one hundred American colleges and universities at a single point in time, and we examine the roles of user attributes-gender, class year, major, high school, and residence-at these institutions. We investigate the influence of common attributes at the dyad level in terms of assortativity coefficients and regression models. We then examine larger-scale groupings by detecting communities algorithmically and comparing them to network partitions ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
307
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(320 citation statements)
references
References 53 publications
11
307
1
1
Order By: Relevance
“…Facebook social networks of California Universities. Using the space of graphlets of size k = 4, Caltech is noticeably different than others, which is consistent with the findings in (Traud et al, 2012).…”
Section: Applicationssupporting
confidence: 88%
See 2 more Smart Citations
“…Facebook social networks of California Universities. Using the space of graphlets of size k = 4, Caltech is noticeably different than others, which is consistent with the findings in (Traud et al, 2012).…”
Section: Applicationssupporting
confidence: 88%
“…In our case, we use k = 4. The figure shows Caltech noticeably different than others, consistent with the results in (Traud et al, 2012) which shows how Caltech is well-known to be organized almost exclusively according to its undergraduate "Housing" residence system, in contrast to other schools that follow the predominant "dormitory" residence system. The residence system seems to impact the organization of the social community structures at Caltech.…”
Section: Large-scale Graph Comparison and Classificationsupporting
confidence: 86%
See 1 more Smart Citation
“…Firstly, we present our experimental results on synthetic graphs from the LFR benchmark [11,12]. Secondly, we evaluate our algorithms on 100 Facebook friendship networks [34]. We start by describing our experimental setup and the used scoring and then continue with the results on the synthetic and the real-world networks.…”
Section: Methodsmentioning
confidence: 99%
“…We thus look for real traces of social networks that have the same characteristics as the one exhibited in [6]. We found that the Facebook social network of the Smith College (MA) [8] is very close to Xfire, especially the average social degree (around 65 connections per user). This social network contains 2,970 users.…”
Section: Simulation Settingmentioning
confidence: 99%